Marketing Plan: Sentir Aveiro - Graça, Ana Margarida Costa Barroca da (2017)
The aim of this master thesis was the elaboration and development of a marketing plan for the tours company, Sentir Aveiro. Its main objectives were increase the company’s sales and its brand awareness. Besides these, increase the number of international partnerships and online comments and reviews were important goals as well. The collection of primary and secondary data allowed to reach many important insights and conclusions about Sentir Aveiro and the tourism industry. To support this plan, it was necessary to make a deep analysis of the external and internal environment of the Sentir Aveiro market. Thus, this master thesis presents an implementation proposal composed by a strategic plan - segmentation, targeting and positioning, and by a set of actions within the marketing mix, highlighting the communication ones hence its importance in the marketing-mix on services and especially on tourism. Within the proposed actions, these are the main ones: the creation of packages for companies, be present on international tourism fairs, change the after-sale process, be present on the online tours platform Viator, creation of an online newsletter, having a different communication and content on Facebook and Instagram, offer and sell Sentir Aveiro merchandising, uniformize the dress code of the guides and establish a partnership with the University of Aveiro.